2012
DOI: 10.3178/hrl.6.70
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to flood risk assessment in Asia-Pacific region based on MRI-AGCM outputs

Abstract: Abstract:Climate change is anticipated to escalate flood impacts, and thus it is important to assess flood risk closely in terms of extent and location. This study aimed to assess present and future flood risks, particularly flood risk change, over the Asia-Pacific region with consideration of climate change impacts by using a topography-based analysis method. By analyzing the output of the super-high-resolution global atmospheric general circulation model, it was found that future flood risk will increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In the Bangladesh portion of the GBM basin, the 0.45 km FID model simulated the flood water level and estimated potential flood inundation depth and area using flood peak discharges of a selected return period produced at each BTOP grid (Kwak et al, 2012). The FID model is a GIS-based model developed from about 0.5 km HydroSHEDS data set (Lehner et al, 2008) and converts flood peak discharges to flood river water levels using a synthetic rating curve developed with Manning's equation (Kwak et al, 2012).…”
Section: Fid Model In Bangladeshmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Bangladesh portion of the GBM basin, the 0.45 km FID model simulated the flood water level and estimated potential flood inundation depth and area using flood peak discharges of a selected return period produced at each BTOP grid (Kwak et al, 2012). The FID model is a GIS-based model developed from about 0.5 km HydroSHEDS data set (Lehner et al, 2008) and converts flood peak discharges to flood river water levels using a synthetic rating curve developed with Manning's equation (Kwak et al, 2012).…”
Section: Fid Model In Bangladeshmentioning
confidence: 99%
“…The FID model is a GIS-based model developed from about 0.5 km HydroSHEDS data set (Lehner et al, 2008) and converts flood peak discharges to flood river water levels using a synthetic rating curve developed with Manning's equation (Kwak et al, 2012). The FID simulated flood water levels of the 10-year return period discharge were considered as DWLs, which include height of embankments.…”
Section: Fid Model In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results of flood hazard assessment described in Part 1 of this study, we selected 50-year flood as extreme events based on MRI-AGCM3.2S (SRES A1B scenario) precipitation for the present and future climates simulated with a distributed hydrological Block-wise TOP model (BTOP model: Takeuchi et al, 2008) and the GIS-based Flood Inundation Depth (FID) model (Kwak et al, 2012). Then, nationwide flood risk change between the present and future climates was estimated in terms of flood hazard (inundation area, depth and frequency) and exposure (affected people and agricultural damages).…”
Section: Approach To Flood Risk Assessmentmentioning
confidence: 99%
“…Especially, Asia is disproportionally influenced by the impacts of flood disasters (WWAP, 2009). For instance, Kwak et al (2012) demonstrated that the Asian region would be at a higher flood risk throughout the 21st century than ever before, because more extreme rainfall would lead to increase of flood inundation depth in many areas.…”
Section: Introductionmentioning
confidence: 99%